Multidisciplinary Approach to the Prevention, Detection, Investigation and Prosecution of Environmental Crime as a Standard of Directive 2024/1203 - Turanjanin, Veljko (Glasnik Advokatske komore Vojvodine, 2026)
By adopting Directive (EU) 2024/1203 on the protection of the environment through criminal law, the European Union has established a new, unified and comprehensive standard in the field of environmental criminal law. This legal instrument, adopted on 11 April 2024 and entering into force on 20 May of the same year, replaces the earlier Directives 2008/99/EC and 2009/123/EC, significantly expands the catalogue of criminal offences, strengthens sanctions, and introduces innovative mechanisms of implementation. One of its key novelties is the requirement for a multidisciplinary approach to the prevention, detection, investigation, and prosecution of environmental crime. The Directive is grounded in the recognition that environmental crime is inherently complex, often cross-border and transnational in nature. Unlawful emissions of hazardous substances into air, water and soil, trafficking in endangered species, illegal waste management, unlawful logging, and improper handling of dangerous substances all inflict severe damage on ecosystems and human health while generating high illegal profits. For this reason, alongside legal and criminal procedural instruments, the integration of knowledge and resources from multiple disciplines—law, criminology, ecology, chemistry, biology, toxicology, economics and information technologies—is indispensable. The Directive explicitly emphasises the obligation of Member States to ensure adequate professional staff and financial, technical and technological resources for combating environmental crime. This includes not only increasing the capacity of the police, prosecution services and courts, but also their specialisation and continuous training. In this context, multidisciplinary teams—bringing together legal experts, forensic specialists, environmental inspectors, information system experts and scientists from the natural and technical sciences—become a necessary condition for effective detection and proof of environmental offences. Furthermore, the Directive highlights the importance of coordination and cooperation not only within a single Member State (between various institutions) but also at the level of the European Union. It underscores the roles of Eurojust, Europol, the European Public Prosecutor’s Office (EPPO) and the European Anti-Fraud Office (OLAF) in providing technical and operational support. Such an approach presupposes that combating environmental crime cannot rely solely on criminal prosecution, but requires the integration of preventive measures, administrative sanctions, civil liability and criminal law instruments into a coherent system. The multidisciplinary approach also includes the participation of the public and non-governmental organisations, which the Directive recognises as part of the standard of access to justice and transparency. Article 15 ensures procedural rights for individuals and associations protecting the environment, thereby creating space for citizens and civil society to contribute to the protection of the public interest. The Directive thus confirms that contemporary environmental crime cannot be effectively addressed without the integration of knowledge and cooperation among diverse disciplines and actors. The multidisciplinary standard it explicitly endorses represents a core element of the European criminal law system for environmental protection and a model that will, in the process of harmonisation, strongly influence candidate countries for EU membership.